War dog - Booth, Martin (Puffin London, 2000)
Jet is trained by her master to be a poacher's dog. When her master is sent to prison Jet is taken into the army - it is early 1939 - to be a military dog. Jet survives Dunkirk, the Blitz and the invasion of Italy, and is finally reunited with the poacher as he lies wounded on the battlefield.